Analysis of the possibilities of artificial intelligence for investigation of fraud - Dmitriy S. Klyuev; Alexander B. Smushkin; Yulia V. Sokolova; Sergey E. Platonov (Физика волновых процессов и радиотехнические системы, 2023)
Background. As a result of the digitalization of society, the number of fraudulent activities using information and telecommunication technologies is growing. The technological complexity of the investigation is such that it requires the use of similar tools in investigative and operational-search activities. Such tools can be artificial intelligence.